Nongenetic Risk Factors of Severe Hypospadias: A Case-Control Study - Vita Indriasari; Rizki Diposarosa; Yoni Fuadah Syukriani; Dedi Rachmadi (Wolters Kluwer Medknow Publications, 2024)
Background: Various risk factors were contributed to hypospadias and may be varied by region and hypospadias severity. The study aims to analyze the nongenetic risk factors associated with severe hypospadias in a provincial referral hospital in West Java, Indonesia. Methods: A case-control study was conducted in hypospadias patients and boys with normal penis treated in our institution during 6-month period. Risk factors of hypospadias were compared between severe and mild hypospadias and the control group and analyzed with Chi-square/Fisher exact test and multivariate logistic regression analysis (P < 0.05 = significant). Results: We studied 84 subjects consist of 46 hypospadias patients (severe: 30 and mild: 16) and 38 control groups. Maternal workplace, primipara, age >35 years old, overweight, the absence of nausea, hypertension, bleeding, alcohol, cigarette smoking, medication, and vegetarian during pregnancy, as well as prematurity, were not significantly different between groups. The use of hormonal contraception and low birth weight infants were significantly higher in severe hypospadias (P = 0.033; P = 0.023; respectively). Multivariate logistic regression analysis showed that hormonal contraception, primipara, and age >35 years old were the risk factors of severe hypospadias (P = 0.008; P = 0.003, P = 0.049, respectively). Conclusions: Hormonal contraception, primipara, and maternal age >35 years old are among the nongenetic risk factors of severe hypospadias in West Java.